Development of a core outcome set for pediatric chronic intestinal failure - Demirok, Aysenur; Nagelkerke, Sjoerd C. J.; Benninga, Marc A.; Köglmeier, Jutta; Mutanen, Annika; Arnell, Henrik; Felcht, Judith; Guimber, Dominique; Wahlstedt, Christina; Avitzur, Yaron; Lambe, Cécile; Tabbers, Merit M. (Journal of parenteral and enteral nutrition, 2023)
Background In research on pediatric chronic intestinal failure, heterogeneity in reported definitions and outcomes exists. This leads to a risk of reporting bias and impossibility of evidence synthesis. Also, reported outcomes should be relevant to both healthcare providers and patients and their parents. Therefore, the aim of this study is to create a core outcome set (COS) to be used in studies on pediatric chronic intestinal failure. Methods Candidate outcomes were selected from a recent systematic review. A three-round Delphi study among key stakeholders and a consensus meeting with an expert panel were undertaken to achieve consensus on the COS. Results Seventy-two stakeholders (79%) completed all three rounds of the Delphi process. Ninety-eight outcomes were assessed, and five new outcomes were added after the first round. Ten outcomes were included in the final COS: weaning from parenteral nutrition, growth, mortality, central line-related infection, central line longevity, sepsis not related to central line infection, central line-related thrombosis, intestinal failure-associated liver disease, (serious) adverse events, and health-related quality of life. Conclusion This pediatric chronic intestinal failure COS consists of 10 outcomes important for all key stakeholders. Usage of this set in future research should minimize outcome heterogeneity and enhance the value of evidence synthesis. This will lead to better management in this field of rare gastrointestinal conditions.
Online veröffentlicht: 22. Dezember 2022
Gesehen am 17.07.2024